Rhegmatogenous retinal detachment due to a macular hole in a patient with pars planitis: a case report - Stavrakas P; Androu AA; Tranos P; Kontou E; Milia M; Georgalas I (Dove Medical Press, 2014)
Panagiotis Stavrakas,1 Angeliki A Androu,1 Paris Tranos,2 Evgenia Kontou,1 Maria Milia,1 Ilias Georgalas3 12nd Department of Ophthalmology, University of Athens Medical School, Attikon University General Hospital, Athens, Greece; 2Ophthalmica Clinic, Thessaloniki, Greece; 31st Department of Ophthalmology, G Genimatas General Hospital, Athens, Greece Abstract: We report a rare case of rhegmatogenous retinal detachment due to a full-thickness macular hole in a young patient with pars planitis. This study was an interventional case report. A 38-year-old Asian man presented with acute reduction of vision in his left eye. His past ocular history revealed a precedent of two intravitreal steroid injections in his left eye, and fundoscopy revealed a total bullous retinal detachment along with 360° snowbanking at the pars plana. Precise preoperative visualization of the posterior pole was impossible due to a dense nuclear cataract. During surgery, an unexpected full-thickness macular hole with no associated epiretinal membrane was observed, which resulted in the retinal detachment. This case of chronic pars planitis complicated with a full-thickness macular hole resulting in retinal detachment was successfully treated with vitrectomy, internal limiting membrane peeling, and perfluoropropane tamponade. Visual acuity improved from hand movements to 6/36 Snellen at 12 months postsurgery. This case report illustrates the rare but possible association between pars planitis with macular hole formation and subsequent retinal detachment, underlying the beneficiary outcome of vitrectomy surgery both diagnostically and therapeutically. Keywords: retinal detachment, macular hole, pars planitis, vitrectomy